Pemeliharaan dan Pelestarian Bahan Pustaka di Perpustakaan SMA Negeri 7 Padang - Destia, Vonny; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper is aimed to describe about the maintenance and preservation of library materials in SMAN 7 Padang dealing with: (1) the factors that caused damage in library materials in SMAN 7 Padang, (2) how to prevent the damage to library materials in SMAN 7 Padang, (3) the constraints faced in the maintenance and preservation of library materials SMAN 7 Padang.Data were collected through observation and interviews with librarians in SMANegeri 7 Padang then from other materials that are supportive. From the analysis and discussion of the study, the result was found as the following: First, the damage of library materials in SMANegeri 7 is caused by factors of physics, biology, chemistry, and humans. Second, the maintenance of library materials in SMANegeri 7 Padang has been done but not optimal yet, such as cleaning the books from dust by using a feather duster and wipe dry. Third, SMANegeri 7 Padang does not have professional staff and also lack of funds to maintenance.Based on the conclusion above, it is suggested as follows. First, it should have professional librarians there. Second, the school should pay more attention to the library by providing the funds for maintenance of library materials. Keywords: library preservation